Analysis of 17 polyphenolic compounds in organic and conventional legumes by high-performance liquid chromatography-diode array detection (HPLC-DAD) and evaluation of their antioxidant activity. (4th July 2018) - Giusti, Federica; Caprioli, Giovanni; Ricciutelli, Massimo; Torregiani, Elisabetta; Vittori, Sauro; Sagratini, Gianni
Abstract: Consumption of legumes has become popular among health-conscious consumers due to the high levels of nutrients such as proteins, dietary fibres, minerals, vitamins and micronutrients like polyphenols. Ten legumes cultivars organically and conventionally grown were compared regarding their chemical profiles in terms of total phenolic content (TPC), total anthocyanin content (TAC), total flavonoid content (TFC) and their antioxidant capacity. The chemical profiles (i.e. free phenolics and anthocyanins) were determined with aid of new high-performance liquid chromatography-diode array detection (HPLC-DAD) method able to identify two individual anthocyanins and 15 polyphenols. Results showed that phenolic acids, namely gallic acid, caffeic acid, syringic acid and ferulic acid, are mainly significantly higher in the organic samples with respect to the conventional ones. All organic legumes showed a higher antioxidant capacity with respect to conventional samples with the exception of red and yellow dehulled lentils.